The Effects of Collision Energy and Isotope on Stereodynamics for the Reactions $O^++H_2/D_2/T_2$ (Journal of Atomic and Molecular Sciences, 2015)
The vector correlations between products and reagents for the chemical reactions $O^++H_2/D_2/T_2$ at different collision energies (1.0eV-2.8eV) have been studiedby means of the quasi-classical trajectory (QCT) method based on the RODRIGO potentialenergy surface(PES) [Rodrigo et al 2004 J. Chem. Phys. 120 4705]. The four generalizedpolarization-dependent differential cross-sections (PDDCSs)$(2π/σ)(dσ_{00}/dω_t),$ $(2π/σ)(dσ_{20}/dω_t),$ $(2π/σ)(dσ_{22+}/dω_t)$ and $(2π/σ)(dσ_{21-}/dω_t)$ have also been calculatedat seven different collision energies respectively. The isotope effect comparingwith the effect of collision energies has been discussed further. The results indicatethat the reaction is sensitive to the mass factors. Meanwhile the collision energies havea greater effect than the mass factors.
Keywords: Stereodynamics; Vector correlation; Quasi-classical trajectory method; Polarization-dependent differential cross-section; Isotope effect.